The British are coming…! A bibliometric analysis of L2 vocabulary research in 1988 - Meara, Paul (LingBaW. Linguistics Beyond and Within, 2020)
This paper uses a co-citation analysis to examine the research on L2 vocabulary acquisition that was published in 1988. Two analyses are presented. The first is a detailed account of the 1988 research on its own terms. The second analysis places this work in a larger context by looking at the research published in a five-year window covering 1984–88. The analyses identify important themes in the research and significant sources who are influencing the way the research is developing at this time. A particularly important new research theme centred around corpus linguistics appears in the 1988 data, and there are some surprising changes to the list of influential sources.